Aplikasi Tiktok Sebagai Media Pendidikan Membentuk Generasi Tangguh Bencana - Feby Nurliana; Suwarno Suwarno (UM Purwokerto Press, 2022)
Insights about disaster mitigation are needed by the people of Indonesia. Basically, disaster mitigation can be embedded in the world of education. Project-based learning assisted by the Tik Tok application can be a medium of learning as well as an effective means of socialization in order to form a generation that is resilient to disasters. Although the Tik Tok application comes with a negative predicate from the community, the average generation Z children currently use it. The purpose of this study is to find out that project-based learning assisted by the tik tok application media can form a generation that is resilient to disasters from an early age. The researcher uses a qualitative method in the form of Research and Development (R&D), namely research that is followed up with the development and dissemination of a learning media through the cycle process of Action, Reflection, Evaluation, Replication, and Innovation. The subjects of this study were students of class VIIIB SMP Negeri 3 Kawunganten Cilacap, totaling 30 students. Data collection techniques used are observation, interview and documentation techniques. While the data analysis technique is qualitative analysis to determine the increase in students' creative thinking. The instrument is used to see the creative thinking ability of class VIIIB students during social studies learning. From the observations of 30 students that have been carried out, it shows that for the very high category there are 20 students, for the high category 5 students, for the medium category 3 students, for the low category 2 students. From these data, the findings obtained are that social studies learning with project based learning assisted by the tik tok application media can improve students' creative thinking in creating a generation that is resilient to disasters.